Cover Feature: Polyanionic Frameworks in the Lithium Phosphidogermanates Li2GeP2 and LiGe3P3 – Synthesis, Structure, and Lithium Ion Mobility (Z. Anorg. Allg. Chem. 3/2020). Issue 3 (13th February 2020) - Eickhoff, Henrik; Sedlmeier, Christian; Klein, Wilhelm; Raudaschl‐Sieber, Gabriele; Gasteiger, Hubert A.; Fässler, Thomas F.
Abstract : Solid electrolyte materials are crucial for the development of high‐energy‐density all‐solid‐state batteries (ASSB) and recently we discovered lithium phosphidosilicates and phosphidogermanates as a novel compound class for lithium ion conductors comprising SiP4 and GeP4 building units. In the here represented structure of Li2 GeP2 two interpenetrating networks of vertex‐sharing Ge4 P6 P4/2 super‐tetrahedra host Li ions in cavities and channels. The two unconnected networks are highlighted with green and orange color. The mobility of lithium ions in this compound class depends on the condensation degree of the tetrahedral building units. Graphic parts reproduced with the kind permission of Dr. Kerstin Mayer. More details can be found in the Article by Henrik Eickhoff, Christian Sedlmeier, Wilhelm Klein, Gabriele Raudaschl‐Sieber, Hubert A. Gasteiger, and Thomas F. Fässler on page 95 ff.